Efficiency and sustainability in multimodal supply chains - Jean-Paul Rodrigue (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper describes approaches in intermodal supply chain management that aim to balance efficiency with sustainability requirements set by firms' corporate social responsibility commitments and society more generally. It explores how accreditation systems can help support green logistics efforts and outlines the competitive advantages and disadvantages of adopting these approaches.
Keywords: 330